Bicarbonate therapy in diabetic ketoacidosis - (:unkn) unknown (COMENIUS UNIV, 2008)
In the treatment of diabetic ketoacidosis (DKA), the aggressive management of hyperglycemia, avoidance of hypoglycemia, and anticipation of the diabetic systemic complications improve patient outcome. In past, the bicarbonate therapy in DKA has been advocated. Yet, no prospective randomized studies on the use of bicarbonate in DKA with arterial pH values <6.9 have been published. However, the bicarbonate therapy in DKA has several potentially deleterious effects including worsening of hypokalemia and intracellular acidosis. Here we present a patient with DKA pH <6.9, treated with bicarbonate, who demonstrated a clinical benefit (Ref. 11). Full Text (Free, PDF) www.bmj.sk.
Keywords: diabetic ketoacidosis; hyperglycemia; bicarbonate; HYPERGLYCEMIC CRISES; SODIUM-BICARBONATE; MANAGEMENT; IMPROVE